Fiscal decentralization and macroeconomics stability nexus: Evidence from the Sub-national governments context of Ethiopia - Million Adafre Bushashe; Yitbarek Bayiley (Cogent Economics & Finance, 2023)
AbstractThis study aimed to investigate the effects of fiscal decentralization on Ethiopia’s regional (Sub-national) macroeconomic stability. The study followed a causational research design employing data from 2005–to 2018. The units of analysis in the study are sub-national governments (SNGs). The study utilized the two-step System General Methods of Moment (SYS-GMM) model since it resolves econometric issues, including endogeneity, autocorrelation, and Heteroscedasticity. The study findings revealed that revenue and composite decentralization have significantly shielded macroeconomic instability. In contrast, expenditure and fiscal dependency are significantly aggravating macroeconomic instability. Among the control variables used in the study, regional economic growth and school enrollment significantly reduce macroeconomic instability; Foreign Direct Investment (FDI), population growth, unemployment rate, welfare, and public investment claimed the opposite effect on macroeconomic stability. The primary implication is that the federal government needs to give fiscal autonomy to SNGs since fiscal dependency is causing macroeconomic instability. Expenditure decentralization is also exacerbating macroeconomic instability; it is essential to have a mechanism to engender budget constraints and make SNGs accountable for their expenditure. Besides, to grasp the shielding effect of revenue decentralization from macroeconomic instability, there should be incentive devices to boost SNG’s tax collection efforts. Since capital and welfare expenditures exacerbate macroeconomic instability, the study urges the government to follow a contractionary fiscal policy by cutting its expenditure. Finally, as opposed to prior studies, the present study used multiple fiscal decentralization indicators, making the study more thorough and closing the knowledge gap.